The Diagnostic Ability of Ganglion Cell Complex Thickness-to-Total Retinal Thickness Ratio in Glaucoma in a Caucasian Population - Almila Sarıgül Sezenöz; Sirel Gür Güngör; Ahmet Akman; Caner Öztürk; Şefik Cezairlioğlu; Mustafa Aksoy; Meriç Çolak (Türk Oftalmoloji Dergisi, 2020)

(untitled)
Objectives:To evaluate the diagnostic accuracy of the macular ganglion cell complex-to-total retinal thickness (G/T) ratio in a Caucasian population.Materials and Methods:A total of 86 patients were enrolled in this cross-sectional study. Patients were divided into 4 groups: healthy; ocular hypertension; preperimetric glaucoma; and early glaucoma. Macular ganglion cell complex (mGCC) thickness, total retinal thickness, and retinal nerve fiber layer thickness (RNFLT) in one randomly selected eye of each patient were measured with measured with Heidelberg HD spectral domain optical coherence tomography (Heidelberg Engineering, Inc., Heidelberg, Germany). G/T ratio (%) was calculated as (mGCC thickness / total retinal thickness) ×100. The ability of each parameter to diagnose glaucoma was examined by area under the receiver operating characteristic curve (AUROC) analysis and sensitivity evaluation at a fixed level of specificity. Unpaired t test was used to compare the measured values between the healthy subjects and the different patient groups.Results:The study included 9 healthy individuals, 18 patients with ocular hypertension, 28 with preperimetric glaucoma, and 31 with early glaucoma. Total retinal thickness, mGCC thickness, RNFLT, and G/T ratio were highest in the healthy group and decreased progressively in patients with ocular hypertension, preperimetric glaucoma, and early glaucoma. All comparisons between the groups were significant for these parameters (p<0.001 for all). Average RNFLT, average GCC, and total retinal thickness showed consistently higher AUROC than G/T ratio in the differentiation between healthy individuals and patients with ocular hypertension, preperimetric glaucoma, and early glaucoma.Conclusion:G/T ratio does not contribute to separation of ocular hypertension, preperimetric glaucoma, and early glaucoma patients from the healthy population. Compared to the other parameters investigated, G/T had lower diagnostic value.